In Silico Study of Phytochemical Compound from Daun Kluwih (Artocarpus camansi) as an Antidiabetic Targeting Aldose Reductase - Radani, Dinar Umaimah; Pintagratia, Ignasia Anindya; Syaiful, Anindya Nursanti; Renaldi, Fahri; Kautsar, Fachrizal Dwi; Novitasari, Dhania (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2026)
Diabetes Mellitus (DM) is a disease characterized by increased blood glucose levels. The most common type of diabetes is type 2 diabetes mellitus. Aldose Reductase is an enzyme that works in the polyol pathway. The polyol pathway is the pathway where glucose is metabolized by aldose reductase into sorbitol. The end result of this polyol pathway will accumulate in the tissue so that there is a disruption of the osmolarity of the basal membrane which can cause complications of diabetes mellitus. Therefore, the activity of the aldose reductase enzyme must be inhibited, one of which is using chemical compounds so that complications such as cataracts do not occur. Tests conducted in this study include Lipinski's RO5, ADMETox, pharmacophore screening, and molecular docking. From the test results, it was found that the most potential compound in treating Diabetes Mellitus is Cycloartenol Acetate.